Using a digital health platform to implement a multi-component CRC screening intervention within a federally qualified health center: study protocol for a hybrid type I trial - Leah Frerichs; Zhang Zhang; Alexis A. Moore; Isabelle Falk; Xianming Tan; Aliza Randazzo; Alison T. Brenner; Daniel S. Reuland; Ajay Dharod; David P. Miller (BMC Health Services Research)
Abstract Background Over the past decade, many well-resourced health plans and systems surpassed the 80% colorectal cancer screening rate goal, while lower resource environments such as federally qualified health centers (FQHCs) lag behind. FQHCs in rural areas are especially challenged with limited resources to reach diverse patients who often lack consistent engagement with clinical care. mHealth solutions, like mPATH®CRC, can address these challenges by automating tasks and expanding patient outreach. This platform identifies patients due for CRC screening, educates them on the commonly used screening tests, and helps them select their best option. This paper describes protocols for a study that will implement mPATH®CRC in FQHCs using a novel outreach strategy that engages patients outside of regular appointments. Methods Following a type 1 hybrid effectiveness-implementation design, we will conduct a patient-level randomized controlled trial (RCT) to assess the effectiveness of mPATH®-CRC over a three-year period. Embedded within the RCT, we will utilize a convergent, mixed methods design for evaluation of the implementation process. The planned trial sample will include 1000 patients who are at average CRC risk and due for screening. Participants will be randomized 1:1 to receive either usual care or outreach through mPATH®-CRC that includes text messages about screening, multi-media education on screening options, and either mailed FIT or assistance to schedule a colonoscopy. The primary outcome is completion of any CRC screening test within six months of randomization. We will also use surveys and interviews with FQHC personnel to explore integration of mPATH®-CRC into clinical workflows and sustainability challenges. Discussion This trial will generate insights into the effectiveness and implementation of a digital CRC screening intervention in resource-limited FQHCs. Findings will inform strategies for optimizing outreach components and scaling implementation in similar settings. Trial registration This trial was registered on June 4, 2024, at ClinicalTrials.gov (identifier NCT06441487).